(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2021)
This article studies textbooks on colonial American history, ranging from the mid-twentieth century to the present. A possible read was made through the history textbooks for secondary school, to examine the representations, changes, permanence and adaptations around the teaching of American history in the period between the 16th and 19th centuries. In addition, textbooks were put into dialogue with texts from the university level which are used in the training of teachers and researchers. In this respect, core issues of the period that are used at different educational levels were compared to see if there is a significant connection between them. This content was examined considering two core concepts for the teaching of history: Historical Thought and Historical awareness. On the other hand, is should be considered, that in no case do we consider that historical thought or historical awareness are exclusively generated from school textbooks. There are other issues such as the historical situation, the teacher and other factors which are central, but textbooks indeed provide elements for a diachronic analysis.